Elements of the Integral Vision of Human Person In The Wednesday Catechesis of John Paul II - Tolo, P. Paulus (Advances in Social Sciences Research Journal, 2018)
Integral vision of human person lies behind of all Church teachings. Pope John Paul II dedicated his life in building a philosophical base the integral vision of human person. His philosophical works heavily owe to Thomistic strands. This study describes the integral vision of human person proposed by John Paul II. The phenomenological method was used to describe actual human experiences and also the experiences of the human being as presented in Sacred Scripture. The findings revealed that some elements of the integral vision of human person are presented to highlight the contribution of John Paul II in unending search for a sound perception of the human person. Looking at the integral vision of human person as such serves modern people in responding to massive propagation of objectivized vision of human person.